CORRELATION OF FAMILY EMOTIONAL SUPPORT AND LEVEL OF PAIN IN CHILDREN ACUTE LYMPHOBLASTIC LEUKEMIA DUE TO CHEMOTHERAPY - Safariah Anggraini; Dyah Trifianingsih (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background : Acute Lymphoblastic Leukemia is a malignant disease in blood-forming organs and is the most common type of cancer in children. In Hemato Oncology Room Tulip III A Ulin Hospital Banjarmasin in 2016 there are 88 children with Acute Lymphoblastic Leukemia. The phenomenon that occurs is the child feels pain due to side effects of chemotherapy. Emotional support of the family to the child is needed, because the positive feeling or energy provided to make children feel safe, peaceful, and loved, so as to reduce or minimize the pain felt by the child.Objective : To know the relation of emotional support of family with level of pain in child Acute Lymphoblastic Leukemia due to chemotherapy in Hemato Oncology Room Tulip III A Ulin Hospital Banjarmasin.Â Method : This research is a quantitative research with cross sectional design. The research population is family and children Acute Lymphoblastic Leukemia who experience pain due to chemotherapy at Hemato Oncology Room Tulip III A Ulin Hospital Banjarmasin. The sample was taken using purposive sampling technique that is 30 respondents. Data collection used questionnaire method and observation sheet. Data analysis used Spearman Rank test analysis at Î± = 0,05.Results : From the 30 respondents who provided emotional support to the acute lymphoblastic leukemia family, 18 respondents (60.0%) often gave emotional support to their families. Level of pain in children Acute Lymphoblastic Leukemia due to chemotherapy of 30 respondents / children who showed moderate pain is 19 respondents (63.3%). Spearman Rank correlation coefficient shows 0,380 significance 0,038 with () 0,05.Conclusion : There is a correlation between the emotional support of the family and the level of pain in children Acute Lymphoblastic Leukemia due to chemotherapy (p = 0.038).Â Keywords : Child, Acute Lymphoblastic Leukemia, Family Emotional Support, Pain Rate